A Foreign Language Mastery Training for International Internship Program Students: English - Suwarno, Bambang; Silaban, Yolanda Novita; Gajah, Nurhamidah; Parapat, Natalia (Jurnal Mitra Prima, 2024)
This foreign language training is conducted on the social sciences and political sciences department campus at the Universitas Muhammadiyah Tapanuli Selatan (UMTS). Foreign language training with the Altissia platform improves students' foreign language skills. The Altissia platform training method has 25 foreign languages ​​using the Common European Framework of Reference for Languages ​​(CEFR) learning method. This foreign language training is used so that students can practice their foreign language skills in preparation for international internships in Asian countries (Malaysia, Singapore) and Europe (England, France, and Germany). Foreign language training with the Altissia platform will determine the ability to write, read, listen, and speak. This language training uses a persuasive method online based on the web, which is applied in the learning process. Before conducting language training, a pre-test is carried out, and after five months of learning, a post-test is carried out. Data collection is carried out based on observations, namely by observing phenomena that occur in the field. The learning training provided to participants includes English training with the Altissia platform method, which involves studying using the platform for at least two hours every day for four days a week. The results from 71 participants, as many as 68 participants, increased their language ability level. Male students are better at English than women